On countable almost invariant partitions of g-spaces - Kharazishvili, A.B. (Український математичний журнал, 2014)
For any σ -finite G-quasiinvariant measure μ given in a G-space, which is G-ergodic and possesses the Steinhaus property, it is shown that every nontrivial countable μ-almost G-invariant partition of the G-space has a μ-nonmeasurable member.